Tuberculosis in US Indigenous Communities: A Need for Public Health Prioritization - Cilloni, Lucia; Dowdy, David W. (American journal of public health (1971), 2024)
Indigenous communities continue to be confronted by health care challenges rooted in a history of colonization and forced displacement. This history is often reflected in less stable living conditions, fewer employment opportunities, lower income levels, and reduced access to food, water, and sanitation services. Geographic isolation, poverty, discrimination, and a lack of cultural understanding on the part of historical colonizers can create structural barriers to health care access among indigenous populations.1 Although racial and ethnic health disparities are increasingly recognized as a major contributor to poor health outcomes in the United States,2 the specific needs of indigenous communities are often underrepresented in efforts to address these disparities. As a result, members of Indigenous communities can experience health outcomes that are often worse even than those of other racial and ethnic minorities (e.g., Black and Hispanic Americans).One striking example of this structural neglect of Indigenous populations is seen in incidence rates of tuberculosis (TB).3 People Identifying as American Indian/Alaska Native (AI/AN) or Native Hawaiian/Other Pacific Islander (NH/OPI) have a TB risk that is more than twice as high as non-Hispanic Black Americans and more than 10 times higher than that of White Americans. These estimates may, in fact, underrepresent the magnitude of the underlying disparities, as multiracial and Hispanic AI/AN individuals have been systematically excluded from corresponding data sets (see Springer et al., p. 226 in this issue of (JPH).